Sosialisasi dan Edukasi Etika Komunikasi Pemasaran di Media Sosial pada Club Panji Sakti (CPS) Singaraja - Kadek Kiki Astria (Jurnal Pengabdian Masyarakat PGSD, 2021)
Social media is a product of technological progress that is currently in great demand by people in various parts of the world, including in Indonesia. Currently, social media is one of the media used for marketing. Marketing activities with online methods are in great demand by business people because of the ease and efficiency of operational costs offered. However, the problem that arises is that the use of social media as a form of marketing strategy is not balanced with the knowledge of online business people about the ethical use of social media in marketing their products. This community service aims to provide educational contributions related to the ethics of marketing communication on social media. This service activity is carried out in the form of education and socialization which is carried out face-to-face with service partners, namely Club Panji Sakti (CPS) Singaraja. The results of the achievement of this socialization and education show that the audience is beginning to understand the existence of marketing communication ethics that applies in social media, the audience has knowledge of what things to do and not to do so as not to violate the applicable ethics, and the audience can apply their knowledge. in marketing activities on social media. Good marketing communication ethics will form a positive image for the audience. In this activity, the audience also understands that self-image also affects increasing sales.